2010
DOI: 10.1007/s11627-009-9267-x
|View full text |Cite
|
Sign up to set email alerts
|

CO2-enriched microenvironment affects sucrose and macronutrients absorption and promotes autotrophy in the in vitro culture of kiwi (Actinidia deliciosa Chev. Liang and Ferguson)

Abstract: In traditional in vitro culture, the low CO 2 concentration inside the vessels restricts photosynthesis and necessitates the addition of sucrose to the culture medium as the main energy source, thus bringing about changes in the absorption of mineral elements from the culture medium. In this study, we investigated macronutrient absorption and sugar consumption in Actinidia deliciosa Chevalier Liang and Ferguson cv. Hayward (kiwi), cultured on medium supplemented with varying amounts of sucrose (0, 10, and 20 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 44 publications
1
9
0
1
Order By: Relevance
“…73 Withdrawal of sucrose from the medium did not favour an increase in fresh and dry masses. This observation is consistent with the findings of Arigita et al with Kiwi explants 55 and Valero-Aracama et al in sea oats 56 under similar culture conditions. The reason behind this was that some cultures require an initial source of carbon from the medium until they are capable of using CO 2 from the vessel headspace as their main carbon source.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…73 Withdrawal of sucrose from the medium did not favour an increase in fresh and dry masses. This observation is consistent with the findings of Arigita et al with Kiwi explants 55 and Valero-Aracama et al in sea oats 56 under similar culture conditions. The reason behind this was that some cultures require an initial source of carbon from the medium until they are capable of using CO 2 from the vessel headspace as their main carbon source.…”
Section: Discussionsupporting
confidence: 93%
“…Similar synergistic effects of combinations of sucrose and CO 2 on in vitro shoot growth were observed in tobacco, 53 Wrightia tomentosa, 31 apple, 54 C. papaya 46 and Actinidia deliciosa. 55 Besides this, it was also observed that liquid medium was superior in overall growth over semi-solid medium in CO 2 -enriched conditions. CO 2 enrichment in liquid culture system was promotory for growth in Uniola paniculata 56 and Musa.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…CO 2 concentration inside the culture vessels decreased when plantlets grown in vitro, which limits the photosynthetic rate of the plants [4, 5]. The biomass accumulation of the in vitro cultured plants increased under photoautotrophic and CO 2 enrichment conditions, also affected nutrient absorption and secondary metabolism [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…In turmeric micropropagation, plant density and medium volume altered the amounts of nutrients used with different optimal mineral solutions required for high and low density cultures [ 20 ]. Sucrose concentration in media affects dry mass and the amount of NH 4 , NO 3 , Ca, Mg, and K taken up [ 22 ]. Multiplication and plant growth responses to plant density varied with medium volume and nutrient availability [ 23 ].…”
Section: Introductionmentioning
confidence: 99%